King of the Wind - Henry, Marguerite, 1902-; Dennis, Wesley; Adams, Barbara Winn; Adams, Susanna; Edith C. Rice Collection of Children's Literature (Chicago : Rand McNally, 1948)
Follows the adventures of the Arabian stallion brought to England to become one of the founding sires of the Thoroughbred breed and the mute Arab stable boy who tended him with loyalty and devotion all his life
Illustrated endpapers
Red cloth; gilt decoration and lettering on upper cover; gilt lettring on spine
Dust-jacket; illustrated in color
Manuscript note on half-title verso: To Suzanna Adams best wishes Wesley Dennis
"Books consulted": p. [175]
Newbery Medal, 1949
Keywords: Arabian horse -- Juvenile fiction; Race horses -- Juvenile fiction